Reclaiming Tawhid in Education: Advancing Global Citizenship, Digital Transformation and Human Rights through Policy Reform (Lembaga Contrarius Indonesia, 2026)
Globalization and the digital era have fundamentally transformed how education engages with diversity, intercultural dialogue and human rights. However, many Muslim-majority contexts continue to rely on secular paradigms that fragment knowledge, weaken spiritual foundations and limit contributions to global citizenship. This study employs a conceptual-analytical qualitative design to propose a Tawhidic model of education management as a policy framework that reclaims education’s divine purpose while addressing contemporary challenges of globalization and digital transformation. The analysis finds that positioning Tawhid as an epistemological core enables the ethical integration of GCED and digital transformation, providing a coherent normative framework for education policy in Muslim-majority contexts. The analysis reveals that by integrating Tawhidic principles with Global Citizenship Education (GCED), Islamic education can serve as a bridge between civilizational values and global human rights frameworks. The paper offers policymakers a pathway toward building inclusive, ethical and future-ready educational systems that advance sustainability in the digital age.